Requirement of Notch in adulthood for neurological function and longevity. - Presente, A.; Andres, A.; Nye, J.S. (Neuroreport, 2001)
Although Notch proteins rely upon presenilins for activation and can modulate neuritic architecture, their role in aging adults and Alzheimer's disease is unknown. Here we examine Drosophila in which Notch function was selectively diminished in adulthood. An outcrossing strategy was employed to reduce the effect of recessive modifiers of lifespan, and a temperature-sensitive allele or inducible dominant-negative Notch transgenes were used to reduce Notch function. A progressive neurological syndrome with loss of flight and shortened lifespan was observed in adults with compromised Notch function. Notch protein persists in aging adult Drosophila brains. However, no evidence of neurodegeneration in the central nervous system was detected. We conclude that Notch activity is constitutively required in the adult fly for neurological function.